(untitled) (International journal of artificial intelligence, 2024)
The aim of the study was to study and evaluate the indicators of erythropoiesis and iron metabolism in patients with anemia of chronic diseases (AHD). The study materials included 92 patients with AHD, 23 of them men, 69 women. Methods - general analysis of blood and morphology of erythrocytes on the photo calorimeter "CFP" 3 position, microscope "Bioline". The biochemical parameters - serum iron, ferritin, transferrin, vitamin B12, folic acid, erythropoietin - were studied on the Roche Hitachi Cobas C 311 apparatus. The study and assessment of iron metabolism in patients with AHD, depending on the nosology of chronic diseases, shows that the level of serum iron has the greatest significant decrease compared with transferrin and ferritin. The assessment of erythropoiesis indices in patients with AHZ, depending on the nosology of the chronic disease, indicates that patients with chronic liver and gastrointestinal diseases have the highest significant changes in folic acid and vitamin B12 indicators compared to.